Death patterns resulting from cell cycle-independent cell death.⁎. Issue 19 (2018) - Imig, Dirke; Kuritz, Karsten; Pollak, Nadine; Rehm, Markus; Allgöwer, Frank
Abstract: Drug-induced cell death on the one hand, and dynamics of the cell cycle on the other hand, represent two well-investigated biological principles. As the cell death machinery is highly regulated and depends on a large number of signaling proteins, a connection to the cell cycle is standing to reason. In recent studies, fluorescent cell cycle marker techniques have been combined with longterm microscopy approaches in order to shed light upon a possible cell cycle/cell death dependency for different death-inducing drugs. Here, we present a simple mechanistic model of the null hypothesis where a cell's cycle does not influence cell death, and calculate death events in different phases of the cell cycle. In a first sample calculation, cells located according to a steady state distribution within the cell cycle are exposed to three different drugs. Dependent on the drug's mode of action, different death patterns are observed. The second sample calculation considers the exposure of synchronized cell populations to one particular drug. Results show that an increase of cell death in G1 can be obtained although cells are initially synchronized in different phases. We conclude that cumulated cell death in one phase can be explained by the stated null hypothesis. Last, the empirical mean and standard deviation are calculated for different sample sizes. Given experimental data, the presented results may help to find out whether the null hypothesis can be rejected.